﻿Proposal (31) to conserve the name Brachypodietalia pinnati Korneck 1974 as a nomen conservandum with a conserved type - Jürgen Dengler; Wolfgang Willner (Vegetation Classification and Survey (VCS), 2023)
After a nomenclatural review of the available names for the order of mesoxeric grasslands within the class Festuco-Brometea, we propose the conservation of the name Brachypodietalia pinnati (with a conserved type) against the names Brometalia erecti and Scorzoneretalia villosae. In syntaxonomic concepts not accepting a single order for the mesoxeric grasslands of Europe, the latter names could still be used, as they are based on different nomenclatural types. (31) Brachypodietalia pinnati Korneck 1974: 123 nom. cons. propos. Typus: Cirsio-Brachypodion pinnati Hadač & Klika in Klika and Hadač 1944 (lectotypus; Dengler et al. 2003: 608; typus cons. propos.). (=) Brometalia erecti W. Koch 1926: 20. Typus: Bromion erecti W. Koch 1926: 121 (holotypus). (=) Scorzoneretalia villosae Kovačević 1959: 7 Typus: Scorzonerion villosae Horvatić ex Kovačević 1959 (holotypus) Syntaxonomic reference: Mucina et al. (2016). Abbreviations: ICPN = International Code of Phytosociological Nomenclature, 4th edn (Theurillat et al. 2021).